A POLÍTICA NACIONAL DE CIÊNCIA, TECNOLOGIA E INOVAÇÃO EM SAÚDE E O ENFRENTAMENTO ÀS DOENÇAS NEGLIGENCIADAS NO BRASIL: INTERESSES E RACIONALIDADES NA AGENDA DE PRIORIDADES E PESQUISA EM SAÚDE - MADUREIRA, Amanda Silva (2020)
This thesis adresses, as na object of its investigation, the analysis of the National Policy of Science, Technology and Innovation in Health and the fight against neglected diseases in Brazil, having as scope the interests and rationales present in the Agenda of Priorities and Research in Health. It was assumed that the constitution of Science, Technology and Innovation in Health Policy in Brazil was a consequence of the effort to consolidate an international guideline that reinforced the concentration of capital and strengthened market failures in health, especially for neglected diseases, made explicit in the recommendations of International Organizations, fragile and sparce. The aforementioned Policy, in this sense, presented itself as a capitalist project of adjustment of the Brazilian State to the pressure of Internacional Organisms, having as main objective the insertion of the country in the global health market. Thus, starting from the comprehensive method, the methodological path started by understanding the determinations of the formulation process of the National Policy on Science, Technology and Innovation in Health, presenting the political-normative panorama that conditioned the institution of the policy, as well as the subjects who influenced the adoption of the National Policy on Science, Technology and Innovation in Health. The fundamentals of the Policy were also addressed, as well as the contradictions between the interests of the market industry and the rationality of the pharmaceutical industry in the face of confrontation neglected diseases. Finally, the process of building the Agenda for Priorites in Health research was demonstrated to face neglected diseases and the persistent reproduction of excluding capital in an international environment that favored the construction of Public Policies under international guidelines.